2001
DOI: 10.1111/j.1572-0241.2001.05272.x
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune hepatitis in African Americans: presenting features and response to therapy

Abstract: In contrast to whites, the majority of African Americans present with cirrhosis. Despite the high prevalence of cirrhosis, the response to therapy is good. However, more immunosuppression is required to control the disease in African Americans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
2
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(68 citation statements)
references
References 18 publications
5
57
2
2
Order By: Relevance
“…Cirrhosis is present at accession more commonly in black North American patients with autoimmune hepatitis than in white North American patients (85% vs. 38%, respectively), and they are younger at presentation than their white counterparts. 14 These findings suggest that black North Americans have a more aggressive disease than white North Americans and that their higher frequency of advanced disease reflects intrinsic disease behavior rather than delays in diagnosis or difficulties in accessing medical care. These implications must be clarified by larger cohort studies that assess racial, genetic, and socioeconomic variables.…”
Section: Racial Regional and Genetic Effectsmentioning
confidence: 78%
“…Cirrhosis is present at accession more commonly in black North American patients with autoimmune hepatitis than in white North American patients (85% vs. 38%, respectively), and they are younger at presentation than their white counterparts. 14 These findings suggest that black North Americans have a more aggressive disease than white North Americans and that their higher frequency of advanced disease reflects intrinsic disease behavior rather than delays in diagnosis or difficulties in accessing medical care. These implications must be clarified by larger cohort studies that assess racial, genetic, and socioeconomic variables.…”
Section: Racial Regional and Genetic Effectsmentioning
confidence: 78%
“…In another study, the dosage of prednisone required at 3 months following initiation of therapy was higher in African Americans than whites, despite similar rates of concomitant immunosuppression with azathioprine. 26 The amount of steroids required to maintain AIH in remission during follow-up was also 3-fold higher in African Americans than whites. At 12 months followup, there was a nonsignificant trend for African Americans to more likely be on azathioprine (74%) compared to whites (48%).…”
Section: Racial Disparities In the Treatment Of Liver Diseasementioning
confidence: 97%
“…Lim et al showed in a single-center retrospective study of 51 patients with AIH showed that African Americans were more than twice as likely to initially present with cirrhosis (85%) compared to whites (38%). 26 Average prothrombin time was also more prolonged among African Americans than whites (16.4 seconds versus 13.5 seconds). In a larger single-center study of 101 patients with AIH, African Americans were more likely than whites to initially present with liver failure (37.8% versus 9.3%, P ϭ 0.001) and more likely to require referral for transplantation (24.3% versus 6.2%, P ϭ 0.009).…”
Section: Racial Variations In Disease Presentationmentioning
confidence: 99%
“…Certain non-white groups of patients including African-American, South American, African and Asian were observed to be younger than their white counterparts at presentation. However in one relatively large multiethnic cohort which included Whites, Hispanics and Asians age at diagnosis was similar among all groups [7,8,15,17,19,35]. The reported female predominance in AIH also was observed as female out-numbered male patients almost 4 folds [7,8,10,17,25,35].…”
Section: Discussionmentioning
confidence: 91%